Performance Evaluation of an Axial Flux PM Motor Based on Finite Element Analysis - (:unkn) unknown (IOS Press, Amsterdam, 2006)
In this paper a performance analysis of an axial flux PM motor based on finite element analysis (FEA) is presented. The quasi-3D method which is adopted for this analysis is consisted of a 2D FEM calculation of the magnetic field in the three dimensional radial domain of the disc motor. The magnetic field distribution is calculated at different armature current and different rotor displacements for all five segments of the motor. Using the results from the FEA the electromagnetic and electromechanical characteristics are going to be presented and a performance evaluation of the motor will be carried out.
Keywords: permanent magnet disc motor, axial flux motor, finite element method, electromagnetic characteristics, electromechanical characteristics